Characterizing phosphorus availability in waste products by chemical extractions and plant uptake. Issue 4 (14th May 2020) - Christiansen, Nina Høj; Sørensen, Peter; Labouriau, Rodrigo; Christensen, Bent T.; Rubæk, Gitte Holton
Abstract: Background: The fertilizer value of phosphorus (P) in waste products relies heavily on its availability to the subsequent crop. Aim: We studied the link between extractable P in waste products and apparent P recovery (APR, i.e ., difference in plant P uptake between P amended and un‐amended soils divided by the amount of P added) using spring barley grown on three sandy soils. Methods: The products included sewage sludge, biomass ash, struvite, compost, meat and bone meal, biochar from sewage sludge, and industrial sludge. Soft rock phosphate and triple‐superphosphate (TSP) were included for comparison. Availability of P was characterized by extraction with water and solutions of sodium bicarbonate, citric acid, oxalic acid, hydrochloric acid, ammonium acetate, ammonium fluoride and anion exchange resin membranes. TSP was used to establish mineral‐fertilizer‐equivalents (MFE). Water and bicarbonate extractions were also applied to products incubated with soil before extraction. Results: The APR ranged 26 to 31% for TSP and 0 to 30% for waste products. APR correlated most strongly with bicarbonate extractable P. The correlation increased when products were incubated with soil before extraction. Conclusions: We conclude that bicarbonate extraction is a good indicator of potential P availability. However, interactions between waste products and soil properties modify P availability.